Flexible Electronics: One‐Step Liquid Metal Transfer Printing: Toward Fabrication of Flexible Electronics on Wide Range of Substrates (Adv. Mater. Technol. 12/2018). Issue 12 (14th December 2018) - Guo, Rui; Tang, Jianbo; Dong, Shijin; Lin, Ju; Wang, Hongzhang; Liu, Jing; Rao, Wei
Abstract : In article number1800265, Rui Gao, Jing Liu, Wei Rao, and co‐workers demonstrate a new kind of one‐step liquid metal transfer printing method with rather wide range substrate adaptability. As illustrated here, a classical Chinese ancient painting (Riverside Scene on Pure Brightness Festival) was thus printed on a picture scroll. With preprinted glue, liquid metal can be selectively patterned on target substrate such as paper to compose various flexible functional electronics.